Noninvasive Left Ventricle Pressure-Volume Loop Determination Method With Cardiac Magnetic Resonance Imaging and Carotid Tonometry Using a Physics-Informed Approach - Liu, Jing; Bilgi, Coskun; Bregasi, Alda; Mitchell, Gary F; Pahlevan, Niema M (IEEE journal of biomedical and health informatics, 2024)
Left ventricular (LV) pressure-volume loop (PV-loop) is an important tool to quantify intrinsic left ventricular properties and ventricular-arterial coupling. A significant drawback of conventional PV-loop assessment is the need of invasive measurements which limits its widespread application. To tackle this issue, we developed a PV-loop determination method by using non-invasive measurements from arterial tonometry and cardiac magnetic resonance imaging. A physics-based optimization strategy was designed that adaptively identifies the optimal parameters to construct the PV-loop. We conducted comparative analysis in a convenience sample (N = 77) with heart failure (HF) (N = 23) patients and a control (N = 54) group to evaluate the sensitivity our PV-loop estimation algorithm. Significant and coherent differences between cohorts for the parameters derived using the PV-loop were observed. Our method captures the significant elevation of LV end diastolic pressure (p<0.001), and the decrease of the ventricular efficiency (p<0.0001) of the HF patients compared to the Control group. This method further captures the mechanistic changes of the LV by highlighting the significant differences of the smaller stroke work (p<0.0001), mean external power (p<0.05), and contractility (p<0.001) between these groups. The LV performance metrics align well with the previous clinical PV-loop observations of HF patients and our results demonstrate that the proposed PV-loop reconstruction method can be used to assess the ventricular functional changes associated with HF. Using this noninvasive method may significantly impact and facilitate the diagnosis and therapeutic management of HF.